Selection of cellulolytic fungi isolated from diverse substrates - Damaso,Mônica Caramez Triches (2012)
The aim of the present work was to select filamentous fungi isolated from diverse substrates to obtain the strains with potential to produce the hydrolytic enzymes. From a total of 215 strains, seven strains from the soils, six from the plants and one from sugarcane bagasse were selected and identified as belonging to the Trichoderma, Penicillium and Aspergillus genera. The best hydrolytic activities obtained by semi-solid fermentation using these strains were approximately: 35; 1; 160; 170 and 120 U/gdm (CMCase, FPase, β-glucosidase, xylanase and polygalacturonase, respectively), demonstrating their potential to synthesize the enzymes compared with the results reported in the literature.